Decoding semanticity of Chinese vocabulary via google translate use / Paramaswari Jaganathan and Lee Pin Ling - Jaganathan, Paramaswari; Lee, Pin Ling (Universiti Teknologi MARA, Kedah, 2015)
The logophonetic feature of Chinese writing makes it a challenge for Chinese-as-a-foreign language (CFL) students to comprehend the semantic of words based on the character alone. This qualitative study aims at analyzing CFL learners’ perception of using Google Translate (GT) and the methods of utilizing GT in their CFL course. Students were given a task-sheet to identify the most suitable meaning in context. This was followed by an interview session to identify how the CFL learners made the selection for words with multiple semantics. The study showed that the respondents generally found GT useful in assisting students to identify the semanticity of words. However, the absence of specific language forms in the Chinese language poses difficulty in the selection of accurate meaning. CFL learners need to acquire the knowledge of Chinese sentence structure, language variation and syntax to utilize GT more effectively in CFL classes, particularly in selecting the accurate meaning for words with multiple semantics. This study provides useful guidance in enhancing a more creative CFL teaching and learning practice in language learning and teaching with the use of GT.